2001
DOI: 10.1046/j.1365-2133.2001.04286.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the efficacy of psoralen plus ultraviolet A therapy for vitiligo enhanced by concurrent topical calcipotriol? A placebo-controlled double-blind study

Abstract: Our results have shown that concurrent topical calcipotriol potentiates the efficacy of PUVA in the treatment of vitiligo, and that this combination achieves earlier pigmentation with a lower total UVA dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 12 publications
(8 reference statements)
3
54
0
Order By: Relevance
“…26 Calcipotriol has also been shown to be 77% effective in treating adults with vitiligo, but there are no data for children with this disease. 27 In the present study, we compared treatment with tacrolimus and clobetasol propionate for repigmenting different areas of the body affected by vitiligo and found very similar results. The risk for adverse effects with both drugs was reduced due to frequent observation and the short duration of the study.…”
Section: Commentmentioning
confidence: 54%
“…26 Calcipotriol has also been shown to be 77% effective in treating adults with vitiligo, but there are no data for children with this disease. 27 In the present study, we compared treatment with tacrolimus and clobetasol propionate for repigmenting different areas of the body affected by vitiligo and found very similar results. The risk for adverse effects with both drugs was reduced due to frequent observation and the short duration of the study.…”
Section: Commentmentioning
confidence: 54%
“…Vitamin D3 alone is not clinically efficient for vitiligo irrespective of its ability to upregulate stem cell factor and endothelin-1 in vitro [2]. The combination of vitamin D3 with phototherapy yield improved results [3,4], thus the current study compared natural UV irradiation with narrowband UVB. Group A achieved better improvement in the delta L score, which represents the skin whiteness between the lesional and peri-lesional area, while the repigmentation rate was not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Activated vitamin D, 1α24(OH) 2 D 3 , is an alternative treatment for vitiligo that accelerates repigmentation through biological interaction between keratinocytes and/or fibroblast to melanocytes [2]. Narrowband UVB is commonly accepted because it provides more effective repigmentation and is less carcinogenic than broadband UVB and calcipotriol along with phototherapy is also very promising [3,4]. On the other hand, solar irradiation following topical use of tacalcitol induces natural repigmentation through the upregulation of c-Kit [5].…”
Section: Brief Reportmentioning
confidence: 99%
“…Some another studies have shown that calcipotriol is 77% effective in treating adults with vitiligo (Ermis et al, 2001;Lepe et al, 2003).…”
Section: Vitamin D Derivativesmentioning
confidence: 99%